Risk of Cardiovascular Events in Survivors of Severe Sepsis - Yende, Sachin; Linde-Zwirble, Walter; Mayr, Florian; Weissfeld, Lisa A.; Reis, Steven; Angus, Derek C. (American journal of respiratory and critical care medicine, 2014)
The risk of cardiovascular events after severe sepsis is not known, and these events may explain increased long-term mortality in survivors of severe sepsis. To determine whether survivors of severe sepsis hospitalization have high long-term risk of cardiovascular events. We examined whether higher risk is due to severe sepsis hospitalization or poor prehospitalization health status, and if the higher risk is also observed in patients hospitalized for infectious and noninfectious reasons, and in other critically ill patients. Unmatched and matched-cohort analyses of Medicare beneficiaries. For unmatched analysis, we compared patients with severe sepsis admitted to the intensive care unit (ICU) and survived hospitalization (n = 4,179) to unmatched population control subjects (n = 819,283). For matched analysis, we propensity-score-matched each patient with severe sepsis to four control subjects (population, hospitalized, non-severe sepsis ICU control subjects, and infection hospitalization). Primary outcome was 1-year incidence rate of hospitalization for cardiovascular events. Cardiovascular events were common among patients discharged alive after severe sepsis hospitalization (29.5%; 498.2 events/1,000 person-years). Survivors of severe sepsis had a 13-fold higher risk of cardiovascular events compared with unmatched control subjects (498.2 vs. 36 events/1,000 person-years; P < 0.0001), and a 1.9-fold higher risk compared with matched-population control subjects (P < 0.0001). Survivors of severe sepsis had 1.1-fold higher risk compared with matched hospitalized patients and infection hospitalizations (P = 0.002 and 0.001) and similar risk compared with matched-ICU control subjects. Survivors of severe sepsis have high risk of cardiovascular events. The higher risk is mainly due to poor prehospitalization health status, and is also seen in a broader population of acutely ill patients.